Partially brain effects of injection of human umbilical cord mesenchymal stem cells at injury sites in a mouse model of thoracic spinal cord contusion - Hu, Haijun; Long, Houqing; Ren, Zhenxiao; Liu, Tianhua; Xu, Jinghui; Xiao, Fan (Frontiers in Molecular Neuroscience, 2023)
Purpose: The pain caused by spinal cord injury (SCI) poses a major burden on patients, and pain management is becoming a focus of treatment. Few reports have described changes in the brain after SCI. Particularly, the exact mechanism through which brain regions affect post-injury pain remains unclear. In this study, we aimed to determine the potential therapeutic mechanisms of pain. A mouse model of spinal cord contusion was established, and molecular expression in the anterior cingulate cortex(ACC) and periaqueductal gray(PAG) in the brain and animal behavior was observed after local injection of human umbilical cord mesenchymal stem cells (HU-MSCs) at the site of SCI. Method: Sixty-three female C57BL/6J mice were divided into four groups: a sham operation group (n=15); a spinal injury group (SCI, n=16); an SCI+HU-MSCs group (n=16) and an SCI+PBS group (n=16), in which the SCI site was injected with HU-MSCs/phosphate buffer. The BMS score was determined, and the von Frey test and Hargreaves test were used to assess behavior every week after surgery. Mice were sacrificed in the fourth week after operation, and samples were collected. The expression of CGRP, Substance P, C-Fos and KCC2 in the ACC and PAG were observed with immunohistochemistry. Chromic cyanine staining was used to observe transverse sections of the injured spinal cord. Result: In the ACC and PAG after SCI, the expression of CGRP, SP and C-Fos increased, and the expression of KCC2 decreased, whereas after HU-MSC injection, the expression of CGRP, SP and C-Fos decreased, and the expression of KCC2 increased. The SCI+HU-MSC group showed better exercise ability from 2-4 weeks after surgery than the SCI/SCI+PBS groups (P<0.001). Local injection of HU-MSCs significantly improved the mechanical hyperalgesia caused by SCI in the fourth week after surgery (P<0.0001), and sensation was significantly recovered 2 weeks after surgery (P<0.0001); no improvement in thermal hypersensitivity was observed (P>0.05). The HU-MSC group retained more white matter than the SCI/SCI+PBS groups (P<0.0001). Conclusion: Local transplantation of HU-MSCs at the site of SCI partially relieves the neuropathic pain and promotes recovery of motor function. These findings suggest a feasible direction for the future treatment of SCI.